Application of quality control circle activities in reducing the incidence of abdominal distention after laparoscopic cholecystectomy (降低腹腔镜胆囊切除术后患者腹胀发生率的品管圈实践) - RAN Maomei (冉茂梅); SHEN Bingying (申冰莹); HE Siming (何思铭); YANG Yuanyuan (杨圆圆); SHAO Jianmin (邵建敏); XU Yuanle (许远乐); PANG Mi (庞咪) (中西医结合护理)
Objective To investigate the effect of quality control circle(QCC) activities in reducing the incidence of abdominal distention after laparoscopic cholecystectomy. Methods Factors influencing the abdominal distention after laparoscopic cholecystectomy were investigated and analyzed, and the problem-solving PDCA procedure was adopted for decision making and countermeasures implementation. Comprehensive interventions such as tube fixation, rehabilitation exercise, enhancing nurse’s scientific literacy, diversified health education, integrative nursing on pain control and establishment of pre-rehabilitant mode were carried out. Results The incidence of abdominal distention was decreased form 67. 28% to 29. 61% after implementation of QCC activities. Conclusion QCC is and effect management tool for reducing the incidence of abdominal distention after laparoscopic cholecystectomy. More efforts should be focused on preoperative and intraoperative issues which could affect the abdominal distention after surgery. (目的 探讨运用品管圈活动降低腹腔镜胆囊切除术后患者腹胀发生率的效果。方法 开展问题解决型品管圈活动, 通过现状分析、原因解析, 制定了针对性对策并予以实施, 包括有效固定管道、合理进行活动等、提升护士科普素养、多元化健康宣教、中西医结合护理缓解疼痛构建预康复模式等。结果 腹腔镜胆囊切除术后患者腹胀发生率从67. 28%下降至29. 61%。结论 品管圈活动能降低腹腔镜胆囊切除术后患者腹胀发生率, 但活动过程中对于术前、术中的改善重点未涉及, 对于围手术期的关注不够全面等问题有待进一步改善。)